PD-L1 inhibition with avelumab for metastatic Merkel cell carcinoma - Gaiser, Maria; Bongiorno, Michelle; Brownell, Isaac (Expert review of clinical pharmacology, 2018)
Introduction: Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin cancer that lacks durable responses to traditional chemotherapy.Areas covered: After MCC was shown to be an immunogenic tumor, small trials revealed high objective response rates to PD-1/PD-L1 checkpoint inhibitors. The JAVELIN Merkel 200 (NCT02155647) trial tested the use of avelumab, a human IgG1 monoclonal antibody against PD-L1, in metastatic MCC. Avelumab recently became the first approved drug for metastatic MCC.Expert commentary: By conducting broad phase I studies assessing the safety of avelumab and a small phase II study demonstrating efficacy in this rare orphan tumor type, avelumab gained accelerated approval for the treatment of metastatic MCC. Additional studies are needed to determine how the antibody-dependent cellular cytotoxicity (ADCC) competent Fc region of avelumab contributes to disease control.Remaining questions: Longer follow-up will determine the durability of checkpoint blockade in controlling metastatic MCC. Additional studies will assess the utility and safety of adjuvant checkpoint blockade in patients with excised MCC. How to increase response rates by combining PD-1/PD-L1 blockade with other treatment approaches needs to be explored. In addition, treatment options for MCC patients who fail or do not respond to avelumab need to be identified.